Challenges of Power Grid in Remote Areas and Their Alternative Solutions - Pongoh, Johan; A. Rumbajan, Virnhie; R. Sattu, Jetli; Walujan, Rainer; F. Tangkuman, Wesly (Cerdika: Jurnal Ilmiah Indonesia, 2026)
Access to reliable electricity remains a significant global challenge, particularly in remote and isolated regions where geographical barriers, high infrastructure costs, and limited technical resources hinder the expansion of conventional power grids. In Indonesia, despite achieving a high national electrification rate, several frontier, outermost, and disadvantaged (3T) regions continue to experience limited access to electricity, adversely affecting social development, healthcare services, education, and local economic activities. This study aims to identify the principal challenges associated with power grid development in remote areas and to analyze alternative solutions based on sustainable renewable energy technologies. This research employed a qualitative descriptive approach through a literature review of scientific articles, government reports, and international energy publications related to rural electrification, renewable energy, and decentralized power systems. The findings reveal that the challenges of rural electrification are driven by interconnected factors, including difficult geographical conditions, high capital and operating costs, limited technical capacity, dependence on fossil fuels, and inadequate policy support. Renewable energy solutions, particularly solar photovoltaic (PV) systems, micro-hydropower systems, and hybrid microgrids, were identified as feasible alternatives for improving electricity access in remote communities. Furthermore, community participation, technical capacity building, and supportive government policies were identified as critical factors for ensuring long-term sustainability. This study concludes that integrated renewable energy-based electrification strategies provide a more sustainable and practical approach to addressing the challenges of electricity access in remote areas. The findings contribute to energy planning and policy development by providing recommendations for achieving equitable, reliable, and environmentally sustainable electricity access in remote regions.